The allocation of additional slots for the FIFA World Cup - Krumer, A.; Moreno-Ternero, J. D. (Journal of Sports Economics, 2023)
How to select participants for a sports tournament when they are divided into different sets, and one should find a fair number of slots for each set? We propose to address this question by resorting to standard tools from the fair allocation literature. To frame our discussion, we focus on the increase in the number of participating teams in the FIFA World Cup. We explore the allocation of additional slots among continental confederations. We consider 10 different allocations. Based on our analysis, we can argue that the European soccer confederation (UEFA) has a solid basis to claim for additional slots.